Analysis of the impact of mobile robots on the efficiency of warehousing and transport processes in modern textile manufacturing - Karabegović Isak (Tekstilna industrija)
The modern textile industry is increasingly confronted with demands for faster delivery, greater production flexibility, and optimized inventory management. Traditional warehousing and transport systems struggle to keep pace with the dynamics of today's market, prompting a growing number of companies to adopt Autonomous Mobile Robots (AMRs) as a solution to enhance operational efficiency and competitiveness. AMRs leverage advanced technologies such as LiDAR sensors, SLAM algorithms, artificial intelligence, and IoT systems to navigate complex industrial environments autonomously, optimize routes, and execute tasks without direct human intervention. In textile manufacturing-where materials continuously move through multiple processing stages-this form of automation brings significant advantages. The implementation of mobile robots enables real-time tracking of material flow, automated inventory control, and a reduction in production downtime. Through integration with ERP and MES systems, AMRs become part of a comprehensive digital ecosystem that facilitates precise planning and data-driven decision-making. Studies indicate that the deployment of AMR technology can improve warehouse efficiency by up to 40% and reduce operational costs by as much as 25%, while also decreasing human error and enhancing workplace safety. Global trends suggest that mobile robots will become standard components of smart textile factories, particularly in advanced economies heavily investing in digital transformation and automation. The integration of mobile robotics into logistics processes within the textile sector yields measurable benefits in terms of efficiency, flexibility, and cost reduction. By leveraging cutting-edge technologies, AMR systems are emerging as key enablers of modern, agile, and sustainable production systems.